Tissue Expander–associated T Cells: Relevance to Breast Implant–associated Anaplastic Large-cell Lymphoma. Issue 3 (23rd March 2022) - Shiokawa, Ichiro; Sato, Takuya; Ogawa, Youichi; Nagasaka, Yuka; Ishikawa, Aoha; Shimada, Shinji; Kawamura, Tatsuyoshi; Momosawa, Akira
Abstract : Background: The generation of breast implant–associated anaplastic large-cell lymphoma (BIA-ALCL) is closely associated with textured implants. The phenotype of BIA-ALCL cells is well examined, but its cell of origin remains unknown. Here we investigate what types of T cells are recruited and differentiated in the surrounding capsules and tissues as a consequence of continuous contact with a textured surface. Methods: Capsule and pericapsule tissues were recovered from patients who had textured or smooth tissue expanders (TEs). These samples were enzymatically digested, and T cells in the samples were analyzed using flow cytometry. Peripheral blood mononuclear cells from the same donors were utilized as a control. Results: Effector memory CD4 + T cells predominantly infiltrated capsules and tissues without apparent differences between textured and smooth TEs. In these effector memory CD4 + T cells, CD4 + resident memory T cells were generated by smooth TEs but not by textured TEs. However, TNFRSF8/CD30 mRNA expression is higher in the CD69 − effector memory CD4 + T cells than in the CD69 + ones. Conclusion: Textured and smooth TEs differentially recruit and/or differentiate T cells in situ.